Impedance analysis of BaMo1−xWxO4 ceramics. (June 2015) - Bouzidi, C.; Sdiri, N.; Boukhachem, A.; Elhouichet, H.; Férid, M.
Highlights: Novel BaMo1− x W x O4 materials were prepared with good dielectric loss properties. Our compound has a high dielectric constant and a good conductivity at low and high frequency. The activation energy of dc conductivity is minimal when the W amount is a maximum. Abstract: The materials BaMo1− x W x O4 ( x = 0.00, 0.05, 0.10, 0.15 and 0.20) were prepared by solid state reaction method. XRD analysis showed that the prepared samples crystallize in tetragonal structure with a preferred orientation of the crystallites along (1 1 2) direction. The values of optical band gap and Urbach energy are in the ranges 2.21–2.44 eV and 77.82–151.51 meV, respectively. Their impedance analysis have been determined in frequency and temperature range of (40–10 6 Hz) and (30–800 °C) respectively. The Nyquist diagrams were investigated in terms of equivalent circuits due to resistors and constant phase elements (CРE). Complex impedance analysis showed the behavior of a dielectric relaxation non-Debye type. We found that resistance of the compounds decreases with temperature, which is related to the electrical conductivity improvement. Conductivity measurements using σ ac were performed on compact pellets of these materials. The ac conductivity versus frequency shows Jonscher's universal power law. In order to study the activation energy versus temperature, we have chosen the small polaron hopping (SPH) model. The obtained activation energy values ranges from 0.29 to 1.08 eV. The dielectric constant ( ε ) and dielectric loss (tan δ ) decreased with frequency, however the ac conductivity ( σac ) increased.